Application of RFID attendance system using PIC18F4580 microcontroller - Norlia Binti Embong (RedWhite Press, 2022)
This project was created to track student attendance using the Radio Frequency Identification (RFID) system. Previously, the lecturer had to record the student's attendance on paper. There were numerous issues with students being able to cheat by attending lectures while using paper. By using RFID and a student card to automatically sign attendance, this project can assist lecturers in reducing such issues. The design is divided into four major sections: the power section, the input unit (RFID reader and RFID tag), the control section, and the output unit. The MPLAB X IDE and PROTEUS software were used for all simulations. The findings indicate that the lecturer can account for the presence of students in the classroom. When students enter the classroom, they must swipe their student ID.